2005
DOI: 10.1248/bpb.28.1711
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Human Hepatic Cytochrome P450 Isoforms to the Metabolism of Psychotropic Drugs

Abstract: The metabolic activities of six psychotropic drugs, diazepam, clotiazepam, tofisopam, etizolam, tandospirone, and imipramine, were determined for 14 isoforms of recombinant human hepatic cytochrome P450s (CYPs) and human liver microsomes by measuring the disappearance rate of parent compounds. In vitro kinetic studies revealed that V max /K m values in human liver microsomes were the highest for tofisopam, followed by tandospironeϾclotiazepamϾimipramine, diazepam, and etizolam. Among the recombinant CYPs, CYP3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 17 publications
0
31
1
Order By: Relevance
“…6). Niwa et al, using only recombinant P450 isoforms (12), similarly reported that tandospirone was metabolized by CYP3A4, but in the present study we were able to demonstrate its primary involvement using human liver microsomes, and also could specifical1y indicate each primary pathway of tandospirone metabolism via CYP3A4 and CYP2D6 by determining the major metabolites in our inhibition study (Fig. 6).…”
Section: Inhibition Study Of the Metabolic Activity Of Tandospirone Ucontrasting
confidence: 37%
“…6). Niwa et al, using only recombinant P450 isoforms (12), similarly reported that tandospirone was metabolized by CYP3A4, but in the present study we were able to demonstrate its primary involvement using human liver microsomes, and also could specifical1y indicate each primary pathway of tandospirone metabolism via CYP3A4 and CYP2D6 by determining the major metabolites in our inhibition study (Fig. 6).…”
Section: Inhibition Study Of the Metabolic Activity Of Tandospirone Ucontrasting
confidence: 37%
“…5,15) Many of the psychotropic drugs, including fluoxetine (a selective serotonin reuptake inhibitor, SSRI), imipramine (a tricyclic antidepressant and a serotonin and noradrenaline reuptake inhibitor), and desipramine (a noradrenaline reuptake inhibitor), are metabolized by CYP2D and/or inhibit the CYP2D-mediated metabolic activities. 8,15,[19][20][21][22][23] One of the dopamine uptake sites in the brain displays high affinity for dopamine uptake inhibitors such as mazindol, a noradrenaline reuptake inhibitor. 24,25) The other site displays rather high affinity for piperizine derivatives and has been termed the piperazine acceptor site.…”
mentioning
confidence: 99%
“…Kinetic constants were determined for all of the enzymes that demonstrated the potential to metabolize tofisopam, CYP1A2, CYP2C9, CYP2C19, CYP3A4, and CYP3A, plus CYP2C8, which was indicated in a previous study (Niwa et al, 2005) as being involved in the metabolism of racemic tofisopam. To ensure that the experimentally determined rates were conducted under initial rate conditions, the amount of recombinant P450 was reduced from 5 pmol to 2 pmol and the incubation time was decreased from 15 min to 5 min.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, this is the first report of stereoselective metabolism of tofisopam. A recent study using recombinant P450 evaluated the ability of individual isozymes to metabolize a number of psychotropic drugs, including racemic tofisopam (Niwa et al, 2005). The study followed tofisopam depletion; thus, no information was given about the metabolites generated.…”
Section: Discussionmentioning
confidence: 99%